2019
DOI: 10.32828/mdj.v14i1.763
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status in Relation to Nutritional Status among 9 years old school Children in Dewanyiah City/Iraq

Abstract: Background: Although they are not life threatening, dental caries and periodontaldisease are the most predominant and widely spread oral diseases throughout theworld. The aims of the study included the investigation of the prevalence andseverity of dental caries, gingivitis and dental plaque in relation to gender,furthermore, nutritional status was assessed in relation to oral health condition(dental caries).Materials and Methods: This oral health survey was conducted among primaryschool children aged 9 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…5 Several studies were conducted in Iraq investigating the nutritional status in relation to various variable. [6][7][8][9][10] Few were found that investigated the teeth eruption status. In 2008, Gatta et al clarified that tooth emergence is a process of growth and therefore is related with other body processes, especially child's weight and height.…”
Section: Methodsmentioning
confidence: 99%
“…5 Several studies were conducted in Iraq investigating the nutritional status in relation to various variable. [6][7][8][9][10] Few were found that investigated the teeth eruption status. In 2008, Gatta et al clarified that tooth emergence is a process of growth and therefore is related with other body processes, especially child's weight and height.…”
Section: Methodsmentioning
confidence: 99%